If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(6-2x)=40+5x
We move all terms to the left:
2(6-2x)-(40+5x)=0
We add all the numbers together, and all the variables
2(-2x+6)-(5x+40)=0
We multiply parentheses
-4x-(5x+40)+12=0
We get rid of parentheses
-4x-5x-40+12=0
We add all the numbers together, and all the variables
-9x-28=0
We move all terms containing x to the left, all other terms to the right
-9x=28
x=28/-9
x=-3+1/9
| 3x−15+3x+11+7x+15=180 | | 2(6-3x)=40+5x | | 86-y=220 | | 15-x=2(x+4) | | 5x+5(4x-2)=90 | | 1000=20x+10 | | -5.2+n=-60 | | x+x+10+5=550 | | 4(2x-1)-x-4=-4 | | x+x10+5=550 | | 4x+3x=17.50 | | d+3/2=2 | | d+32=2 | | 2(6x-48)+2(4x+38)=360 | | -1.1g+5=12.7 | | 4(2x-10)=3(x+10) | | 2(-7+8n)=14+2n | | (x+11)+(x+4)=180 | | 4(x+5)-9=17 | | 108=12x10 | | 7t–31=9t-45 | | 28-x=3x+16 | | 7y+27+3y+71=180 | | -2(x-3)+4x=-1(-x+1) | | k^2=6 | | 7v-37=4v-16 | | (9x+11)=(3x+2x)+(-15+16) | | 2z-38=z | | 5s=s=15+s | | 2s+44=10s-60 | | 2s+44+10s-60=180 | | 3w=7+10 |